Tratamento ambulatorial e hospitalar na monitorização glicêmica de gestantes diabéticas em uso de insulina - Kron, Meline Rossetto [UNESP] (2014)
Objective: To evaluate the effectiveness of outpatient treatment compared to inpatient in prenatal care of pregnant women with diabetes who use insulin during pregnancy . Research design and methods: Randomized Clinical Trial , including all pregnant women with diabetes who used insulin at any time during prenatal care and gave birth at the Faculty of Medicine of Botucatu,São Paulo State University ( HCFMB ) . It was randomized 91 patients: 48 to ambulatory monitoring ( supply of inputs for glucose monitoring ) and 43 for hospital monitoring (conducted through short and frequent hospitalizations ) for collecting glycemic profile. As variables studied were maternal and neonatal outcomes considered and later were condensed into Success / Failure Maternal and Success / Failure of the newborn groups. Results:There was no statistically difference between all maternal - fetal outcomes analyzed,this way showing the effectiveness of outpatient treatment compared to inpatient pregestational care.It certified that maternal success increased the chance of the newborn be well succeed, regardless of the place pregestational was conducted. Conclusion: Outpatient treatment proved to be effective and maternal and perinatal outcomes were similar to those that received hospital treatment. Maternal Success during prenatal care for hospitalized and ambulatory diabetic pregnant women leads to success of the newborn